Overcoming the market/state binary code - Donati, Pierpaolo (Transcending Modernity with Relational Thinking, 2021)
This chapter deals with the recurrent societal crises connected to the processes of globalisation. The argument is that, in order to avoid permanent societal crises, we have to break away from the self-referential logic of the lib/lab configuration of society. Such a new set-up shall be capable of allowing for the emergence of new social subjects that can generate and adopt certain ethical standards of conduct and change the economic-political systems. This transformation should be structural. Niklas Luhmann would say that this is not possible, because - in his view - society operates with autopoietic mechanisms insensitive to social subjectivities. The chapter challenges Luhmann's sociology by showing why and how the emergence of a new society is as possible as it is necessary.